Discrimination - Trends and Cultural Features - Danailova, Irina (Research Papers, 2020)
50 years after the adoption of the first official documents demonstrating how the political and economic will eliminate different treatment in labour and occupations based on gender, race, religion, political beliefs and sexual preferences, the debate on lack of discrimination is still up to date. The aim of this paper is to clarify the importance of values and culture for improving accessibility to work, opportunities for education and training in countries where discrimination in labour and social life is observed. The main conclusions are that overcoming discriminatory practices is directly linked to actions in the field of national cultures – the creation of new value systems that could lead to a lasting change in individual behaviour, and hence - of the whole community and country.